Environmentally sustainable versus aesthetic values motivating millennials' preferences for wine purchasing: Evidence from an experimental analysis in Italy - Gianluigi Gallenti; Stefania Troiano; Francesco Marangon; Paolo Bogoni; Barbara Campisi; Marta Cosmina (Agricultural and Food Economics, 2019)
The interest in wine produced in an environmentally friendly manner is increasing in the global market among both consumers and producers. Moreover, numerous labelling and certification systems have been introduced to guarantee environmentally friendly production. Consumers can consider some environmental attributes in relation to their purchasing decisions as components of their ethical demands; such consumer behaviours can drive wine production to more sustainable models. This change depends on many factors, such as consumers' willingness to pay for sustainable and ethical attributes and the effective communication of such attributes. Among consumers, young people belonging to the so-called millennial generation are the new wine consumers, and they represent an increasingly important segment of the global wine market. This study uses a choice experiment to investigate Italian millennials' preferences toward two ethical attributes of wine: 'carbon footprint claim' and 'winescape aesthetic'. The findings show considerable heterogeneity among respondents, the majority of whom seem to be interested in the carbon footprint claim, even if a group of them prefer to pay a premium price to consume high-quality wines. Our results indicate that winescape aesthetic does not appear to be an important attribute in guiding respondents' preferences.
Keywords: 330; Wine consumption; Carbon footprint; Winescape aesthetic; Choice experiment; Italian millennial generation